Porous spherical LiMnPO4·2Li3V2(PO4)3/C cathode material synthesized via spray-drying route using oxalate complex for lithium-ion batteries. (20th October 2015) - Zhang, Jia-feng; Wang, Xiao-wei; Zhang, Bao; Tong, Hui
Graphical Abstract: Highlights: Porous spherical LiMnPO4 ·2Li3 V2 (PO4 )3 /C was synthesized via spray-drying route. The lithium ion diffusion path was shortened. The contact area between electrode and electrolyte was increased. The mutual doping phenomenon existed between LiMnPO4 and Li3 V2 (PO4 )3 . Electrochemical performance of porous composite was significantly improved. Abstract: Porous spherical LiMnPO4 ·2Li3 V2 (PO4 )3 /C composite was synthesized innovatively via spray-drying route using oxalate complex. X-ray diffraction patterns and energy dispersive X-ray results revealed that the composite was composed of LiMnPO4 and Li3 V2 (PO4 )3 . Scanning electron microscopy results revealed the porous spherical structure, and transmission electron microscopy (TEM) results exhibited that the surface of the microsphere was coated with carbon layer of about 5.1 nm thickness. The mutual doping phenomenon between LiMnPO4 and Li3 V2 (PO4 )3 was also confirmed by high resolution TEM and Fourier transform observation. Porous spherical LiMnPO4 ·2Li3 V2 (PO4 )3 /C delivered an initial capacity of 132.6 mAh g −1 at 0.1 C and noticeably enhanced high rate capacities at 1, 3 and 10 C. Compared with solid spherical LiMnPO4 ·2Li3 V2 (PO4 )3 /C, cycle performance, high-rate performance and lithium ion intercalation performance of porous spherical LiMnPO4 ·2Li3 V2 (PO4 )3 /C were all significantly improved.